PENCEMARAN AIR DAN STRATEGI PENGGULANGANNYA - Herlambang, Arie (Center for Environmental Technology, 2006)
The rapid growth of population in developing country causes environmental contamination by increasing significantly pollution load inÃ‚Â river and other water body. It needs efficient and effective strategy to overcome contamination in certain areas. Technical identification of pollution source and its influence to environmental quality is important to should be known and socialized to community. Land use to is important to getÃ‚Â priorityÃ‚Â and should beÃ‚Â managed consistently environmentally sound, beside solid waste and domestic wastewater. Law enforcement also should be applied, especially to company or industry which significantly gives contribution to environmental degradation. Environmental restoration need fund, so government as regulator need partnerÃ‚Â from private to overcome environmental problem. Environmentally based industries and services is needed to be developed as government counterpart, but up to now the development of them retarded caused by non competitive interest of commercial bank. Environmental fund should be collected from polluter through regulated mechanism and In the next futureÃ‚Â environmental bank should possible manage the fund and finance environmental industry and services to overcome environmental pollution, in this case government act as regulator only.Key words : water polution, management, water resources, strategies